Antioxidant genes and susceptibility to air pollution for respiratory and cardiovascular health - Fuertes,E; van,der Plaat D; Minelli,C (Free Radical Biology and Medicine, 2020)
Oxidative stress occurs when antioxidant defences, which are regulated by a complex network of genes, are insufficient to maintain the level of reactive oxygen species below a toxic threshold. Outdoor air pollution has long been known to adversely affect health and one prominent mechanism of action common to all pollutants is the induction of oxidative stress. An individual's susceptibility to the effects of air pollution partly depends on variation in their antioxidant genes. Thus, understanding antioxidant gene-pollution interactions has significant potential clinical and public health impacts, including the development of targeted and cost-effective preventive measures, such as setting appropriate standards which protect all members of the population. In this review, we aimed to summarize the latest epidemiological evidence on interactions between antioxidant genes and outdoor air pollution, in the context of respiratory and cardiovascular health. The evidence supporting the existence of interactions between antioxidant genes and outdoor air pollution is strongest for childhood asthma and wheeze, especially for interactions with GSTT1, GSTM1 and GSTP1, for lung function in both children and adults for several antioxidant genes (GSTT1, GSTM1, GSTP1, HMOX1, NQO1, and SOD2) and, to a more limited extent, for heart rate variability in adults for GSTM1 and HMOX1. Methodological challenges hampering a clear interpretation of these findings and understanding of true potential heterogeneity are discussed.